1990
DOI: 10.1073/pnas.87.8.3190
|View full text |Cite
|
Sign up to set email alerts
|

Molybdopterin guanine dinucleotide: a modified form of molybdopterin identified in the molybdenum cofactor of dimethyl sulfoxide reductase from Rhodobacter sphaeroides forma specialis denitrificans.

Abstract: The nature of molybdenum cofactor in the bacterial enzyme dimethyl sulfoxide reductase has been investigated by application of alkylation conditions that convert the molybdenum cofactor in chicken liver sulfite oxidase and milk xanthine oxidase to the stable, well-characterized derivative [di(carboxamidomethyl)Jmolybdopterin. The alkylated pterin obtained from dimethyl sulfoxide reductase was shown to be a modified form of alkylated molybdopterin with increased absorption in the 250-nm region of the spectrum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 28 publications
1
87
1
Order By: Relevance
“…Extraction of pterins from CO dehydrogenase with SDS and subsequent carboxamidomethylation with iodoacetamide followed published procedures [28]. Isocratic HPLC of pterins was on a reverse-phase C 18 column (ET 250/8/4 Nucleosil 120-7 C18, Macherey & Nagel) with photodiode-array detection (model 991, Waters).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of pterins from CO dehydrogenase with SDS and subsequent carboxamidomethylation with iodoacetamide followed published procedures [28]. Isocratic HPLC of pterins was on a reverse-phase C 18 column (ET 250/8/4 Nucleosil 120-7 C18, Macherey & Nagel) with photodiode-array detection (model 991, Waters).…”
Section: Methodsmentioning
confidence: 99%
“…The mobile phase was 50 mM ammonium acetate, pH 6.8, at a flow rate of 1 ml min Ϫ1 . Dicarboxamidomethyl molybdopterin cytosine dinucleotide [di(cam)MCD] was quantified spectrophotometrically employing ε 367 ϭ 7.34 mM Ϫ1 cm Ϫ1 [28]. Reaction of MCD to form A with I 2 /KI or to pterin-6-carboxylic acid with alkaline permanganate followed published procedures [29].…”
Section: Methodsmentioning
confidence: 99%
“…Except for dinitrogenase, all molybdocnzymes studied appear to contain molybdopterin [1][2][3]. Much is known about the structure of molybdopterin and one of' its precursors [4,5] and about genes involved in its biosynthesis [2,6-9] but proteins involved in the pathway from early precursors and molybdate to the final incorporation of MoCo into apoenzymes are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the structure of an FdhD homologue in the d-proteobacteria Desulfotalea psychrophila has been solved (DpFdhD; pdb code 2PW9, unpublished) and revealed that it has structural homologies with the cytidine deaminase family of nucleotide-interacting proteins 13 . As nucleotides are chemical moieties of the Mo-bisPGD structure 14 , it has been hypothesized that EcFdhD could bind and sulphurate the cofactor before its insertion into FDHs 11 . A recent study supports this hypothesis with the copurification of Mo-bisPGD onto FdsC, an FdhD homologue from Rhodobacter capsulatus 15 .…”
mentioning
confidence: 99%